2013
DOI: 10.1186/1752-153x-7-63
|View full text |Cite
|
Sign up to set email alerts
|

Limit of detection and limit of quantification development procedures for organochlorine pesticides analysis in water and sediment matrices

Abstract: BackgroundReliable values for method validity of organochlorine pesticides determination were investigated, in water by solid phase extraction and in sediment by Soxhlet extraction, followed by gas chromatography equipped with an electron capture detector. Organochlorine pesticides are categorized as Persistent Organic Pollutants. Hence, critical decisions to control exposure to these chemicals in the environment are based on their levels in different media; it is important to find valid qualitative and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(46 citation statements)
references
References 45 publications
0
45
0
1
Order By: Relevance
“…wastewater influents or effluents, ground-, surface-and tap waters) and various solid samples (sediment, sludge, biological matrices). Sample preparation techniques can enhance the performance results for better recovery, increased sensitivity and lower detection limits [63].…”
Section: Methods In Detection Of Steroidal Edcsmentioning
confidence: 99%
“…wastewater influents or effluents, ground-, surface-and tap waters) and various solid samples (sediment, sludge, biological matrices). Sample preparation techniques can enhance the performance results for better recovery, increased sensitivity and lower detection limits [63].…”
Section: Methods In Detection Of Steroidal Edcsmentioning
confidence: 99%
“…Limits of detection (LOD) and of quantification (LOQ) are the most important values that researchers look for when considering method validity. 11 Limit of Detection (LOD) and Limit of Quantification (LOQ) were calculated according to Seal (2016). In this study, the recovery percentage was calculated as follow as Recovery (%) = (Concentration found -Concentration Applied) divided with 100% and result showed that recovery percentage (%) for standard compounds is more than 99%.…”
Section: Validation Methods Of Phenolic Acid By Using Hplc Analysismentioning
confidence: 99%
“…In the present study, the limit of detection (LOD) and limit of quantification (LOQ) were estimated at a signal to the noise ratio of 3:1 and 10:1, respectively. Studies done by Saadati et al (2013);Singh (2013) and Tian et al (2014) suggested that LOD and LOQ were determined based on the response and slope of a specific calibration curve obtained. Based on the standard calibration curve in Figure 7, the standard calibration curves of imazapic and imazapyr were linear for 1 to 5 mg L -1 concentration, with the coefficient of determination (R 2 ) above 0.99.…”
Section: Linearity Limit Of Detection (Lod) Limit Of Quantificationmentioning
confidence: 99%